Comparative Analysis Study of Front-End JavaScript Frameworks Performance Using Lighthouse Tool - Mangapul Siahaan; Vincent Octarian Vianto (Jurnal Mantik, 2022)
JavaScript is one of the most widely known and widely used programs. The most common determining factor when choosing the proper framework for a job. Through a comparative analysis of several JavaScript frameworks like React, Angular, Vue, Svelte, and SolidJS, this research aimed at understanding how web applications perform. As part of this research and to compare JavaScript Framework, system development used SDLC Waterfall for each framework to build Weather App. According to the performance testing results, The FCP value of the five frameworks has a score of fewer than 1,8 seconds. The SI value of the five frameworks is less than 3.4 seconds. The LCP value of the five frameworks is less than 4 seconds. The TTI value of the five frameworks is less than 3.8 seconds The TTI value of the five frameworks is less than 3.8 seconds. Based on the results of the analysis and testing conducted in this research using Google Lighthouse, Vue delivers the best performance when implementing the Weather App.